Fiduciary duty and corporate social responsibility: Evidence from corporate opportunity waiver - Boyd, Naomi; Li, Shenru; Wang, He (Helen); Wang, Xianjue (Journal of Banking & Finance, 2025)
This paper examines whether corporate social responsibility (CSR) aligns with shareholder interests or stems from agency conflicts. To explore this, we utilize the staggered adoption of state-level Corporate Opportunity Waiver (COW) laws, which potentially weaken the fiduciary duty of loyalty among directors and officers, thereby exacerbating agency conflicts. Through a difference-in-differences analysis, we find that CSR activities significantly decrease following the enactment of COW laws. This decline is more pronounced in firms with weaker corporate governance, greater external opportunities for directors and officers, less incentivized CEOs, and those operating in less competitive industries. Additionally, our results show that the positive effect of CSR on financial performance is diminished by the adoption of COW laws. These findings support the value-enhancing perspective of CSR and highlight the importance of fiduciary duty of loyalty in promoting CSR.